2017
DOI: 10.1007/s00414-017-1736-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of DNA transfer onto clothing during regular daily activities

Abstract: Low levels of DNA from an unidentified human source, often referred to as trace DNA, are ubiquitous, can be transferred onto objects by either direct or indirect methods and have an unknown longevity in situ. Clothing items from crime scenes are often submitted for trace DNA analysis, usually in attempt to identify a person of interest. This study examined the transfer of DNA onto three 10 × 10 cm areas located on the front, back and shoulder of an individual's external clothing (n = 300) during a regular day'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Personal items and clothing are often collected as evidentiary or reference material. It is usually assumed that these will provide the profile of the regular user/wearer, which they usually do; however, they often also contain DNA from other sources [64,82,104,123,137,[160][161][162][163][164]. For example:…”
Section: Prevalence and Origin Of Non-self Dna On Personal Itemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Personal items and clothing are often collected as evidentiary or reference material. It is usually assumed that these will provide the profile of the regular user/wearer, which they usually do; however, they often also contain DNA from other sources [64,82,104,123,137,[160][161][162][163][164]. For example:…”
Section: Prevalence and Origin Of Non-self Dna On Personal Itemsmentioning
confidence: 99%
“…Although both van den Berge [104] and Kamphausen et al [192] concluded that DNA persistence and transfer in a washing machine is very unlikely, further studies have found different results. Of unworn items washed in household washing machines with normal loads of dirty laundry, Voskoboinik et al [194] found that 19% gave single-source or major DNA profiles matching that of a member of the household and Ruan et al [160] found 76% gave single-source or mixed DNA profiles. As suggested by Ruan et al [160], this increase in detection of DNA transfer could be due to the use of a profiling kit with increased sensitivity (PowerPlex21® as opposed to SGM Plus™).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite earlier doubt about the impact of secondary transfer [32], this occurrence has been repeatedly demonstrated and is now widely accepted [48,50,93]. Particularly as testing sensitivity grows, secondary, tertiary and subsequent transfer events produce detectable DNA profiles on items never handled by the DNA contributor; this detection can follow innocuous interaction such as handshakes [94] or co-laundering of clothing [65,95], or even routine movement of people and equipment around a forensic DNA laboratory and office [71].…”
Section: Transfer Of Trace Dna After Initial Depositionmentioning
confidence: 99%